Prematur e Ejaculation and Chronic Bacterial Prostatitis - Islam, Md Shafiqul (Medicine Today, 2017)
Premature ejaculation (PE) is regarded as the most common male sexual disorder. Previous studies reported that prostatic inflammation was highly prevalent in PE. However, the effect of antibiotic treatment of cases with PE and chronic prostatitis has not been extensively investigated. To examine the effect of antibiotic treatment in delaying ejaculation in patients with PE and chronic prostatitis. The study was carried out in my private chamber and at General Hospital N.Gong from June 2014 to December 2016. The study was performed with prior permission and the confidentiality was maintained. A total of 135 consecutive men attending of secondary premature ejaculation (SPE) were included in this study. Sequential microbiologic specimens were obtained from urine and prostatic fluids. Antibiotics were given for one month according to the results of their culture and sensitivity test. All patients were instructed to follow up in General Hospital N.Gong/Private chamber monthly for at least 4 months. At the end of the 4-month follow-up, another prostatic secretion analysis was performed. Based on expressed prostatic secretion culture and white blood cell (WBC) count, 84 (62.2%) were having chronic bacterial prostatitis. The remaining 51 (37.8%) patients had negative WBC count. Of the 84 patients with secondary premature ejaculation (SPE) and chronic bacterial prostatitis, 20 patients were left untreated and considered as a control group. All 64 patients with PE and chronic prostatitis continued the 1- month treatment duration. Following 1-month antibiotic treatment, all 64 patients with initially positive cultures had sterile final cultures (P < 0.05). Fifty one (79.68%) patients showed increases in their ejaculatory latency time and reported good control of their ejaculation and were considered treatment responsive. None of the control group patients experienced any improvement either in their prostatic infection condition or in their ejaculation time. The follow-up of treatment-responsive patients (N = 51) revealed no recurrence of PE with negative prostatic culture. Successful eradication of causative organisms in patients with PE and chronic prostatitis may lead to marked improvement in intravaginal ejaculatory latency time and ejaculatory control. Medicine Today 2017 Vol.29(2): 21-25